7b+2b-1=8b-7

Simple and best practice solution for 7b+2b-1=8b-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7b+2b-1=8b-7 equation:


Simplifying
7b + 2b + -1 = 8b + -7

Reorder the terms:
-1 + 7b + 2b = 8b + -7

Combine like terms: 7b + 2b = 9b
-1 + 9b = 8b + -7

Reorder the terms:
-1 + 9b = -7 + 8b

Solving
-1 + 9b = -7 + 8b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-8b' to each side of the equation.
-1 + 9b + -8b = -7 + 8b + -8b

Combine like terms: 9b + -8b = 1b
-1 + 1b = -7 + 8b + -8b

Combine like terms: 8b + -8b = 0
-1 + 1b = -7 + 0
-1 + 1b = -7

Add '1' to each side of the equation.
-1 + 1 + 1b = -7 + 1

Combine like terms: -1 + 1 = 0
0 + 1b = -7 + 1
1b = -7 + 1

Combine like terms: -7 + 1 = -6
1b = -6

Divide each side by '1'.
b = -6

Simplifying
b = -6

See similar equations:

| a/64=225/480 | | 8x+2=7(x-5)+8 | | -5x-3(-2x+9)=-34 | | -3(1+3x)-2x=6-2x | | 3+(-7)-8= | | 3n-5=2n | | (-3)-2+4= | | 5-3y=3-4y | | 7-(-5)-8= | | 11-13(x-2)=15x-2(x+4) | | -6x+2=20+3x | | 6z-2=z+24 | | (-5)+(-5)-1= | | 8(b+8)=-8+2(7b+3) | | 7y-35/12 | | 5(-3k-6)=-2(6k-2)-7 | | (-2)-2+4= | | 1/x+3/(2x)-(x-2)/(4x)=10 | | h+6+5=2 | | 7-8x+9+4x+5x-5=1+3*5 | | 3/2q+12=7/2q-4 | | 6(x-2.5)=8-6(3.5+x) | | -(x-8)+1=8x+9(1-x) | | 234/4 | | (-2)+(-1)+-(8)= | | 6(3m+5)=-25 | | 5+4(3x-4)=7-5(2x+1) | | -4x+71=-1 | | (mx+qx)(my+qy)=0 | | 5f=48-f | | 7-3x=5x+15 | | 2(7m-2)=8(1+m) |

Equations solver categories